Physical and chemical analysis of commercial nystatin - doi: 10.4025/actascihealthsci.v35i2.12769 (Acta Scientiarum. Health Sciences, 2013)
Nystatin (NYS) is a fermentation-produced antibiotic of the polyene group. Commercial NYS is a mixture of compounds named NIS A1, A2 and A3. Current analysis undertook physical and chemical analyses in two samples of commercial nystatin (NYS I and NYS II). Moisture (Karl Fischer), spectroscopic (IR, UV and fluorescence) and thermal analyses (TGA and DSC) were conducted. The moisture was respectively 9.2% and 8.8% for samples I and II. Absorption spectrum in the UV/VIS region had a vibronic structure with three lmax.. The mirror image rule was not complied with in the fluorimetric analysis. Spectroscopy analysis in the IV region indicated that samples showed spectra similar one to another, analogous to crystal type A. Thermal analyses by DSC provided a wide, single endothermal peak and, therefore, similarities among the samples. DTG shows that samples undergo decomposition at three phases within the temperature range under analysis. Results show that samples are impure and not polymorphic, constituted by a mixture of the compounds A1, A2 and A3.